Vulture funds and the fresh start accounting value of firms emerging from bankruptcy - Gietzmann, M.; Isidro, H.; Raonic, I. (Journal of Business Finance and Accounting, 2018)
We study how distress-oriented hedge funds (vulture funds) play an important role in the fresh start valuation of firms emerging from Chapter 11 reorganization. We find that loan-to-own vultures acquire debt positions of the distressed firm that grant dominant power in the bankruptcy negotiations, and they then use the discretion allowed by fresh start accounting to introduce valuation bias in their favor. We show that the strategic influence over fresh start values can create opportunities to increase vulture investors’ returns at the expense of other claim holders